Tratamiento del desarrollo sostenible en la formación de contadores en Brasil - Vazquez Carrazana, Xiomara Esther (2024)
The attempt of identifying the curricula content of accounting courses in Brazil for studies on sustainable development became the research problem, thus posing the objective to identify the significant nature of core themes on sustainable development in curricula of accounting programs in Brazil. Prior studies revealed a fragmented treatment of sustainable development in accounting science curriculum in the country (Mannes et al., 2018; Rocha et al., 2021; Santos et al., 2021), which evidences by local and global consensus that accountants in training must develop social responsibility as a result of the interconnection of several curriculum components (Alves Cosenza, 2019; Gomes et al., 2012; Gray Collison, 2002; Montilla et al., 2013; Santos et al., 2021). This article supports the interconnection of four core themes: ethics, philosophy, socioenvironmental reports, and human rights. This is an exploratory and documentary research, and the object of study involves 30 curricula of undergraduate Accounting courses offered by Brazilian universities with undergraduate and stricto sensu post-graduate programs. In these curricula compulsory subjects that could cover sustainable development during academic year 2021 were revised. In a general overview, no integral or multidimensional content on sustainability was observed in the curricula, which highlights better results in some other regions of the country.